PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN CV TEGUH KARYA UTAMA SURABAYA - RIZALDI, FAHMI; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Every organization is required to improve their performance. This condition encourage companies to useinformation system is carrying out daily task. The implementation of information system in an organization willaccelerate and simplify the completion of the task by every employee. This condition is expected to improve theperformance of employee in the company. The purpose of this research is to examine the influence of accountinginformation system to the performance of employees on CV Teguh Karya Utama. This research is a quantitativeresearch. The population is the 45 employees of CV Teguh Karya Utama. The data analysis technique has beendone by using simple refression analysis. It can be concluded from the result of the research that theimplementation of accounting information system has significant and positive influence to the performance ofthe employees has been applied in the company properly, the performance of the employees in the company willbe improved as well. The implementation of accounting information system is strongly influenced by the humanresources who are owned by the company. The company should always conduct the competency of the humanresource about information and technology. Competency and knowledge of the human resources is need by thecompany in maximizing the use information technology in CV Teguh Karya Utama.Keywords: performance, accounting information system, and simple linear regression.